Classification of Objects and Human Cognition - Gopinath, M. A. (Journal of Information and Knowledge, 2001)
Shows how classification starts at a very young age of a child and during its learning periods. How cognition helps in classification and as a person grows up how he learns the intricacies of classification. The abilities of classifying objects helps in professional growth. Deals with how our sensory perceptions help in classification.